Regulatory 3′ Untranslated Regions of Bacterial mRNAs - Ren, Gai-Xian; Guo, Xiao-Peng; Sun, Yi-Cheng (Frontiers in Microbiology, 2017)
The untranslated regions (UTRs) of mRNA contain important features that are relevant to the post-transcriptional and translational regulation of gene expression. Most studies of bacterial UTRs have focused on the 5′regions; however, 3′UTRs have recently emerged as a new class of post-transcriptional regulatory elements. 3′UTRs were found to regulate the decay and translation initiation in their own mRNAs. In addition, 3′UTRs constitute a rich reservoir of small regulatory RNAs, regulating target gene expression. In the current review, we describe several recently discovered examples of bacterial regulatory 3′UTRs, discuss their modes of action, and illustrate how they facilitate gene regulation in various environments.